The sentry [compact disc, unabridged] - Crais, Robert (Crais, Robert. Elvis Cole series., 2010)
Dru Rayne and her uncle fled to L.A. after Hurricane Katrina. Now, five years later, they face a different danger. When Joe Pike witnesses Dru's uncle beaten by a protection gang, he offers his help, but neither of them want it and neither do the federal agents mysteriously watching them. As the level of violence escalates, and Pike himself becomes a target, he and Elvis Cole learn that Dru and her uncle are not who they seem and that everything he thought he knew about them has been a lie.